Performing Ecclesiastes: Text as Script - Jeanette Mathews (Religions, 2023)
All biblical scholars are committed to the interpretation of ancient written texts, but Biblical Performance Criticism (BPC) reminds interpreters that performance helps us better understand Scripture. A distinct difference between Narrative Criticism and Performance Criticism is the broader application of Performance Criticism to poetic and prose texts that are not grounded in narrative. The ambiguity of prose and poetry that does not readily identify speakers is open to a range of performative interpretations. Furthermore, audiences are necessary for performance and contribute to meaning-making. The embodied experience of performers and audience alike contribute to the interpretation of biblical texts. This article reflects on a performance of Ecclesiastes translated as a script of a television talk show, claiming that embodying and performing Scripture is itself a method for interpretation. Through the performance of Scripture, we are reminded that interpretation is shared and dynamic within the community of faith.